A retrospective study of magnetic resonance-guided focused ultrasound ablation for uterine myoma in Taiwan - Sheng-Ling Tung; Ting-Ywan Chou; Hung-Shi Tseng; Chi-Ming Lee (Elsevier, 2016)
Objective: To report our experiences with 40 patients who were treated with magnetic resonance-guided focused ultrasound surgery (MRgFUS) for uterine fibroids and their 6-month follow-up status. Materials and Methods: A total of 40 patients with uterine fibroids underwent MRgFUS from January 2009 to November 2011. The Uterine Fibroid Symptoms and Quality of Life Questionnaire was used to determine the patients' Symptom Severity Scores (SSS) prior to and 6 months after treatment. The nonperfused volume (NPV) values and NPV ratio were obtained immediately at the end of the treatment and at 6 months follow-up. Results: No procedure-related complications were noted throughout the 6-month follow-up period among the 40 patients who underwent MRgFUS for uterine fibroids. The mean reduction in SSS in our patients after 6 months was 43.7%, and the mean reduction of fibroid volume was 31.7%. In addition, the mean reduction of NPV and mean NPV ratio was 52.7% and 33.3%, respectively. Conclusion: The results obtained from this study demonstrated that MRgFUS can be safely and effectively used to ablate uterine fibroids to produce a significant decrease in mean fibroid volume and improve SSS for up to 6 months after treatment.